The pattern of lingga village based on history - Berkat Idaman; Shanty Silitonga; Yulianto Qin (Jurnal Teknosains, 2021)
Lingga Village is a tourist village that is well known as a traditional Karo tourism village and has become a major tourism destination in North Sumatra Province. This village still has a legacy of traditional Karo architecture. In ancient times this Lingga village had 80 units of traditional houses. During holidays, tourists visiting this village can reach as many as 300 people from within the country and from abroad. Currently in Lingga Village there are only two units of the Karo Traditional House. The purpose of this research is to model the village pattern of Lingga village based on interview about village’s history. The formulation of the problem that is the focus of this research are; how was the pattern of the villages, how was the orientation of the Karo Traditional House in Lingga Village in the past, how was the circulation of Lingga Village villages in the past. The research method used in this study is the simulation by modeling method. The primary data collection consisted of observing, documenting, and conducting interviews with informants from Lingga Village. Secondary data collection consists of books and journals about Lingga Village. The final result of this research is the model of the pattern of Lingga village based on history. The model focuses on house orientation, circulation patterns and types of traditional houses in Lingga village.